Thermal proteome profiling: Insights into protein modifications, associations, and functions. (December 2022) - Le Sueur, Cecile; Hammarén, Henrik M.; Sridharan, Sindhuja; Savitski, Mikhail M.
Abstract: Tracking proteins' biophysical characteristics on a proteome-wide scale can provide valuable information on their functions and interactions. Thermal proteome profiling (TPP) is a multiplexed quantitative proteomics approach that measures changes in protein thermal stability—a key biophysical property—across different cellular states. Developed in 2014, as a target-deconvolution assay for drugs and other small molecules, TPP has since evolved to a system-level biochemical omics technique providing insights into context-dependent changes in protein states. In this review, we summarise key advances in the experimental and data analysis pipeline that have aided this transformation and discuss the recent developments and applications of TPP. Graphical abstract: Image 1 Highlights: Thermal proteome profiling (TPP) measures thermal stability of proteins proteome-wide. Analysed on the peptide-level, TPP data can reveal functional PTMs and proteoforms. Co-melting of proteins reveals protein complex association. Integration of TPP into multiomic data can be powerful for functional annotation.